The Vikings - Nordeide, Sæbjørg Walaker 1956-2020; Edwards, Kevin J. ca. 20./21. Jh (Past Imperfect, 2019)
‹div›The prevailing image of a Viking is frequently that of a fierce male, associated with military expansion and a distinctive material culture, and the Vikings have maintained a resonance in the popular imagination to the present day. This book presents a fresh overview of the Vikings from both conceptual and material perspectives. In an engaging survey, Sæbjørg Walaker Nordeide and Kevin J. Edwards analyse Viking religion, economic life, and material culture in and beyond the Scandic homelands.‹/div›